SporeSat: a lab on a chip for single cell study and translation to ground applications - Wan Salim, Wan Wardatul Amani (2019)
SporeSat is an autonomous, free-flying spacecraft that was used to conduct a scientific experiment to investigate how germinating plant cells sense and respond to gravity. The plants used in the experiment are single-celled spores of the aquatic fern Ceratopteris richardii. The SporeSat mission was flown using a three-unit (3U) nanosatellite weighing approximately 12 pounds and measuring 14 inches long by 4 inches wide by 4 inches tall. The SporeSat science payload serves as a technology platform to evaluate new microsensor technologies for enabling future fundamental biology missions.